NATURAL DEAF EDUCATION FOR THE COMMUNITY - Puguh Setyo Nugroho; Agustinus Agustinus; William William; Eko Budi Siswidiyanto; Nur Rohmah; Zakiyatul Faizah (Universitas Airlangga, 2022)
Congenital deafness will impact the quality of life of affected individuals if they do not obtain early detection and intervention. Socialization of congenital deafness is needed, thereby the community can engage in early detection and intervention efforts. Socializing about the early detection and intervention of congenital deafness. Educational activities are carried out with counseling using the lecture method, discussion, and pretest and posttest. The average pretest result was 62.03 (± 11.51) and the posttest average was 88.39 (± 13.41). Based on the comparison between the pretest and posttest results, we found a significant difference (p < 0.0001) statistically. Public knowledge of congenital deafness needs to be improved in order to increase community participation in terms of early detection and intervention.